USING DIGITAL FEEDBACK IN TEACHING ARGUMENTATIVE WRITING - Afi Niamah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
Argumentative Writing is the last writing skill given to the fourth semester of English Department students. It equips the students to present convincing argument as well as critical analysis in the form of argumentative essay. Argumentative Writing course is important since it introduces them in elaborating previous studies to support their argument in composing thesis. English Department students of STKIP PGRI Jombang tend to get difficulties in explaining the previous studies critically. As a matter of fact, most students were confused in relating their argument with the previous studies. Terms connecting previous studies indicate that the students are able to compose thesis scientifically. Thus, this study was conducted to show the use of digital feedback by involving both CALL (Computer-Assisted Language Learning) and MALL (Mobile-Assisted Language Learning) in teaching argumentative writing. The improvement of the students’ ability in argumentative writing by using digital feedback is based on at least 15 achievement gain point reached by 80% of the class. The study found that some students need to have face to face consultation in confirming their final draft.